ANALISIS PENGARUH PROFITABILITAS, STRUKTUR MODAL, DAN KONSERVATISME AKUNTANSI TERHADAP KUALITAS LABA DENGAN KEPEMILIKAN MANAJERIAL SEBAGAI VARIABEL MODERATING (Studi pada Perusahaan Manufaktur Sub Sektor Basic Materials Yang Terdaftar di BEI Tahun 2020-20 - Gita, Adellia; Mohklas, Mohklas (Jurnal Ilmiah Fokus Ekonomi, Manajemen, Bisnis & Akuntansi (EMBA), 2025)
ABSTRACTThe purpose of this research is to examine profitability, capital structure and accounting conservatism on earnings quality with managerial ownership as a moderating variable. The population in this research is manufacturing companies in the basic materials sub-sector listed on the IDX in the 2020-2022 period. The sample was selected using the purposive sampling method to produce data on 31 manufacturing companies in the basic materials sub-sector, so the total research data for 3 years was 93 samples. Data collection uses documentation techniques through copying and archiving documents. The data analysis technique uses multiple linear regression and Moderate Regression Analysis (MRA). The research results show that profitability has a significant negative effect on earnings quality. Capital structure and accounting conservatism do not have a significant effect on earnings quality. Managerial ownership cannot moderate the influence of profitability, capital structure, and accounting conservatism on earnings quality.Keywords: Profitabilty, Capital Structure, Accounting Conservatism and Qualitty of Earnings